Testimonies about crimes against Vukovar residents Testimonies about crimes against Vukovar residents Catalog
This tape includes interviews with a 13-year-old female from Vukovar who tells about how she was injured and managed to escape her town. After it Dragutin from Vukovar and Marko Pranjic tell how they were captured, what they were forced to do and how they escaped.